Hospital-acquired conditions occur more frequently in elective spine surgery than for other common elective surgical procedures. (June 2020) - Horn, Samantha R.; Segreto, Frank A.; Alas, Haddy; Bortz, Cole; Jackson-Fowl, Brendan; Brown, Avery E.; Pierce, Katherine E.; Vasquez-Montes, Dennis; Egers, Max I.; Line, Breton G.; Oh, Cheongeun; Moon, John; et al.
Highlights: Elective spine surgery patients experienced an overall HAC rate of 3.3% HACs are more common in elective spine surgery as compared to other common elective procedures. Common HACs in spine surgery are surgical site infection, UTI, and venous thromboembolism. Abstract: Hospital-acquired conditions (HACs) have been the focus of recent initiatives by the Centers for Medicare and Medicaid Services in an effort to improve patient safety and outcomes. Spine surgery can be complex and may carry significant comorbidity burden, including so called "never events." The objective was to determine the rates of common HACs that occur within 30-days post-operatively for elective spine surgeries and compare them to other common surgical procedures. Patients: >18 y/o undergoing elective spine surgery were identified in the American College of Surgeons' NSQIP database from 2005 to 2013. Patients were stratified by whether they experienced >1 HAC, then compared to those undergoing other procedures including bariatric surgery, THA and TKA. Of the 90, 551 spine surgery patients, 3021 (3.3%) developed at least one HAC. SSI was the most common (1.4%), followed by UTI (1.3%), and VTE (0.8%). Rates of HACs in spine surgery were significantly higher than other elective procedures including bariatric surgery (2.8%) and THA (2.8%) (both p < 0.001). Spine surgery and TKA patients had similar rates of HACs(3.3% vs 3.4%, p = 0.287), though spine patients experienced higher rates of SSI (1.4%vs0.8%, p < 0.001) and UTI (1.3%vs1.1%, p < 0.001) but lower rates of VTE (0.8%vs1.6%, p < 0.001). Spine surgery patients had lower rates of HACs overall (3.3%vs5.9%) when compared to cardiothoracic surgery patients (p < 0.001). When compared to other surgery types, spine procedures were associated with higher HACs than bariatric surgery patients and knee and hip arthroplasties overall but lower HAC rates than patients undergoing cardiothoracic surgery.